In vitro regeneration of mulberry (Morus indica L.) by BAP and NAA - Kshirsagar, Ashwinikumar B.; More, Pallavi B.; Pawar, Kiran R. (Current Botany, 2026)
The present study focused on optimizing the in vitro propagation of Morus indica L. (Mulberry) using varying concentrations of BAP (6-Benzylaminopurine) for shoot induction and NAA (Naphthalene Acetic Acid) for root initiation. The experimental design tested six different concentrations of BAP (0.5 to 3.0 mg/L) and NAA (0.5 to 3.0 mg/L) on nodal explants, with observations taken at 27 days after inoculation (DAI). The results revealed that BAP at 2.5 mg/L (T5) significantly enhanced shoot initiation, with a minimum initiation time of 6.5 days and the highest number of shoots per explant (6.75). The maximum shoot elongation (4.6 cm) was also observed in this treatment. For root initiation, the optimal NAA concentration was 2.5 mg/L (T5), which led to the highest rooting percentage (85%) and root length (4.5 cm). The findings demonstrate that a combination of 2.5 mg/L BAP and 2.5 mg/L NAA is most effective for improving both shoot and root development in M. indica, offering a promising protocol for large-scale in vitro propagation of this economically valuable species. This research holds significant importance for the mass production of M. indica plants, facilitating faster multiplication for commercial and environmental uses, including sericulture, where M. indica serves as a primary food source for silkworms. The optimized protocols from this work can be applied to enhance the efficiency of mulberry plant production, meeting the growing demands for quality mulberry plants in agriculture and industry.